The Implementation Of Inquiry-Based Learning InTeaching English To The 8th Grade Students Of SMP N 2Sawit Boyolali In 2015/2016 - Khotimah, Khusnatul, Prof. Dr. Endang Fauziati M. Hum, Aryati Prasetyarini S.Pd, M.Pd (2016)
This study aims at describing the implementation of Inquiry-based Learning in teaching English to the 8th grade students of SMP Negeri 2 Sawit in 2015-2016 academic year consisting of learning objectives, classroom procedures, classroom techniques, the roles of instructional material, teacher roles, student roles, media, and types of assessment. The researcher gets the data of this research from event, informant, and document analysis. This research applies descriptive qualitative research. The subjects of this study are English teacher and the students of the eighth grade at SMP Negeri 2 Sawit Boyolali. The methods of collecting data are observation, interview, and document. The technique of analyzing data is descriptive interactive covering the steps of reduction the data, data display, and conclusion drawing or verification. The result of this study is divided into eight parts. First, for learning objective, there are two kinds of learning objectives namely general learning objective and specific learning objective. Second, the classroom procedures used are exploration, elaboration, and confirmation. Third, the classroom techniques are oral repetition, reading passage, identifying keyword, answering question, free writing, and summarizing. Fourth, the instructional materials used are printed and nonprinted. The roles of instructional material are as a reference source for learners on grammar, vocabulary, pronunciation, as a source of activities for learner practice and communication, as resource of stimulation and ideas for classroom activities. Fifth, the teacher roles are as controller, manager, facilitator, and motivator. Sixth, the student roles are as subject learning, object of learning, performer, learner learns from the teacher, learner learns from other students, learner learns from other teaching sources, monitor and evaluator of his own progress. Seventh, the media used in teaching learning process are picture and board. Eighth, types of assessment used are test and non-test. Test consists of daily test, middle test and final test, while non-test consists of listen and repeat, interactive in the conversation performance, reading outcomes, and constructed response written.